Analisis Faktor-Faktor Yang Mempengaruhi Perpindahan Pelanggan Pada Toko Retail Komputer Usaha Dagang Mitrakom Yogyakarta - -, Mardianto; Sulistyo, Beni Agus; Rumanjaya, Alfredi; Sutanto, Aftoni; Asakdiyah, Salamatun (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
Abstract This study aims to analyze the influence of satisfaction (X1), transfer barriers (X2) and complaints (X3) on the transfer of customers at the Mitrakom Yogyakarta retail business retail store. The analytical method in this study is descriptive research with a quantitative approach that uses regression analysis methods, while the testing stages include validity, reliability, classical assumptions, multiple linear regression analysis, determination coefficient (rsquare), regression coefficients together (f test ) and hypothesis testing (t test ). The population of this research is customers who has conducted transactions at the Mitrakom Yogyakarta retail retail store. The technique of taking research samples is using purposive sampling method. The number of questionnaires distributed amounted to 136 copies. Validity and reliability test results are valid and reliable. Hypothesis testing provides results that simultaneously show the influence of the three variables studied proved to significantly affect the dependent variable of customer displacement. These results indicate that the ups and downs of customer movements at the Mitrakom Yogyakarta trading business shop does not depend on the ups and downs of satisfaction levels, transfer hurdles and complaints obtained by customers. The coefficient of determination (adjusted rsquare) is obtained by 0.630 which indicates that 63% of customer transfers can be explained by its independent variables and the remaining 37% is explained by other factors outside the variables not included in this study. Furthermore, the results of research through statistical analysis have proven the truth of the four hypotheses in this study. Keywords: Satisfaction, transfer barriers, complaints and customer transfers